Innovative Marketing Strategies in Culinary MSMEs: A Case Study of Warkop Agam Medan - Ade Nurhidayah; Ratih Amelia; Yuniar Andi; Hengky Kosasih; Sabaruddin Chaniago (Yayasan Bina Bisnis Nusantara Medan, 2025)
This study aims to examine the marketing strategies implemented to increase sales at Warkop Agam Medan. The research employs a qualitative descriptive method and was conducted at Warkop Agam, located at Jalan Karya Wisata No. 73, Pangkalan Mansyur, Medan Johor District, Medan City, North Sumatra. Data were collected from both primary and secondary sources using techniques such as observation, interviews, and documentation. The analysis involved organizing and interpreting data through a qualitative descriptive approach supported by relevant literature and expert opinions. The findings indicate that: (1) Warkop Agam applies a marketing strategy focused on excellent customer service, consistent product quality, and varied pricing; (2) While annual sales have experienced fluctuations, the overall trend remains stable without significant impact on year-over-year growth; (3) A notable strength is the shop’s strategic location along a major road, contributing to its visibility; and (4) The main weakness lies in limited digital marketing efforts, particularly underutilization of social media platforms such as TikTok, YouTube, Instagram, and food vlogs. This research highlights the importance of integrating traditional marketing with digital strategies to enhance competitive advantage in the culinary MSME sector